Finding solutions where they are: Working with adaptation pioneers to support social learning and scaling of locally-led innovation - Habermann, Birgit; Gichuki, Leah (International Livestock Research Institute, 2025)
As part of the Climate Action Science Program, the pioneers of the adaptation team presented their farmer-led research using a positive deviance approach to the NORAD food system team. The presentation focused on the work with the adaptation pioneers in Kenya and key achievements in social learning and scaling.